Active video games for improving health-related physical fitness in older adults: a systematic review and meta-analysis - Nuannuan Deng; Kim Geok Soh; Borhannudin Bin Abdullah; Hermione Tan; Dandan Huang (Frontiers Media S.A., 2024)
BackgroundThe global population is experiencing a rapid rise in the quantity and percentage of older people. In an effort to enhance physical activity among older adults, active video games (AVGs) are being suggested as a compelling alternative and are currently under scrutiny to evaluate their efficacy in promoting the health of older people.ObjectiveThis review aims to synthesize current studies and formulate conclusions regarding the impact of AVGs on the health-related physical fitness of older adults.MethodsSeven databases (PubMed, Web of Science, SCOPUS, SPORTDiscus, EMBASE, MEDLINE, and CINAHL) were searched from inception to January 21, 2024. Eligible studies included randomized controlled trials examining the effect of AVGs compared to control conditions on health-related physical fitness outcomes in older adults. The methodological quality of the included trials was assessed using the PEDro scale, and the certainty of evidence was evaluated using the GRADE approach. A random-effects model was used to calculate effect sizes (ES; Hedge's g) between experimental and control groups.ResultsThe analysis included 24 trials with a total of 1428 older adults (all ≥ 60 years old). Compared to controls, AVGs produced significant increases in muscular strength (moderate ES = 0.64-0.68, p < 0.05) and cardiorespiratory fitness (moderate ES = 0.79, p < 0.001). However, no significant effects were found for body composition (trivial ES = 0.12-0.14; p > 0.05) and flexibility (trivial ES = 0.08; p = 0.677). The beneficial effects of AVGs were greater after a duration of ≥ 12 vs. < 12 weeks (cardiorespiratory fitness; ES = 1.04 vs. 0.29, p = 0.028) and following ≥ 60 minutes vs. < 60 minutes of session duration (muscular strength; ES = 1.20-1.24 vs. 0.27-0.42, p < 0.05).ConclusionAVGs appear to be an effective tool for enhancing muscular strength and cardiorespiratory fitness in older adults, although their impact on improving body composition and flexibility seems limited. Optimal improvement in cardiorespiratory fitness is associated with a longer duration of AVGs (≥ 12 weeks). Moreover, a session duration of ≥ 60 minutes may provide greater benefits for the muscular strength of older adults.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=482568, identifier CRD42023482568.